Visual function and vision-related quality of life after vitrectomy for idiopathic macular hole: a 12mo follow-up study - Duan, Hong-Tao (Int J Ophthalmol, 2015)
AIM: To investigate the visual function and the relationship with vision-related quality of life (VRQOL) after macular hole repair surgery. METHODS: Prospective case series. Thirty-six consecutive eyes in 36 patients who underwent pars plana vitrectomy (PPV) and internal limiting membrane (ILM) peeling were included. The 25-item National Eye Institute Visual Function Questionnaire (VFQ-25) was answered by the participants before and 3 and 12mo after operation. Follow-up visits examinations included best-corrected visual acuity (BCVA), clinical examination, and central macular thickness (CMT) measured by optical coherence tomography (OCT). RESULTS: Macular-hole closure was achieved in 35 of 36 eyes (97.2%). At baseline and months 3 and 12, the logMAR BCVAs (mean±SD) were 1.15±0.47, 0.68±0.53 (P<0.0001 versus baseline), and 0.55±0.49 (P<0.001 versus baseline, P =0.273 versus month 3), respectively; the CMTs (µm) were 330±81, 244±62 (P<0.001 versus baseline), and 225±58 (P<0.001 versus baseline, P=0.222 versus month 3), respectively; the median preoperative VFQ-25 composite score of 73.50 (63.92-81.13) increased postoperatively to 85.50 (80.04-89.63) at 3mo (P<0.001) and 86.73(82.50-89.63) at 12mo (P<0.001) respectively. The improved BCVA was correlated with improvements in five subscales (r=-0.605 to -0.336, P<0.001 to P=0.046) at 12mo. CONCLUSION: PPV with ILM peeling improved anatomic outcome, visual function, and VRQOL. The improved BCVA was an important factor related to the improved VRQOL.